2005
DOI: 10.1007/11535218_20
|View full text |Cite
|
Sign up to set email alerts
|

On Codes, Matroids and Secure Multi-party Computation from Linear Secret Sharing Schemes

Abstract: Abstract-Error-correcting codes and matroids have been widely used in the study of ordinary secret sharing schemes. In this paper, the connections between codes, matroids, and a special class of secret sharing schemes, namely, multiplicative linear secret sharing schemes (LSSSs), are studied. Such schemes are known to enable multiparty computation protocols secure against general (nonthreshold) adversaries.Two open problems related to the complexity of multiplicative LSSSs are considered in this paper. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 26 publications
1
50
0
Order By: Relevance
“…This algorithm is efficient if the secret sharing scheme itself is efficient to begin with. This follows from the results in [10] where it is shown that strong multiplication linearizes this "decoding problem," by means of a generalization of ideas taken from the Berlekamp-Welch algorithm. For completeness we include in this paper a description of the general procedure from [10] as it applies to our algebraic geometric secret sharing schemes, even though in the present case it also follows by efficient decoding algorithms for algebraic geometry codes.…”
Section: It Is Quasi-threshold (With a 2g Gap) This Means That A Tnmentioning
confidence: 91%
See 2 more Smart Citations
“…This algorithm is efficient if the secret sharing scheme itself is efficient to begin with. This follows from the results in [10] where it is shown that strong multiplication linearizes this "decoding problem," by means of a generalization of ideas taken from the Berlekamp-Welch algorithm. For completeness we include in this paper a description of the general procedure from [10] as it applies to our algebraic geometric secret sharing schemes, even though in the present case it also follows by efficient decoding algorithms for algebraic geometry codes.…”
Section: It Is Quasi-threshold (With a 2g Gap) This Means That A Tnmentioning
confidence: 91%
“…For completeness we show how strong multiplication linearizes the problem of recovering the secret in the presence of corrupted shared. It is a special case of the more general technique given in [10]. But also note that known techniques for decoding algebraic-geometry codes apply here.…”
Section: Corollary 1 a Tn ⊂ A(m)mentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques provided a characterization of the hierarchical access structures that admit an ideal perfect secret sharing scheme [12]. Other relevant results on secret sharing have been obtained by using matroid theory as, for instance, the ones in [2,9,13,23].…”
Section: Introductionmentioning
confidence: 99%
“…Secure multiplication is a fundamental primitive in its own right, as secure multi-party computation is often based on combinations of secure addition and secure multiplication, the latter typically being demanding and involved while the former is typically much more straightforward. Arithmetic secret sharing allows efficient recovery of the secret in the presence of faulty shares, by a generalization of a result from [12] (see Section 5) and also gives rise to verifiable secret sharing [10].…”
Section: Introductionmentioning
confidence: 99%